Pendugaan Nilai Parameter Genetik Berdasarkan Sifat Produksi Pra-Sapih Domba Padjadjaran - Maria Magdalena Kapitan; Veronika Yuneriati Beyleto (Fakultas Pertanian Universitas Majalengka, 2024)
This research on estimating genetic parameters for production traits of pre-weaning Padjadjaran Sheep was conducted at the Village Breeding Center of Neglasari village, Darangdan District, Purwakarta Regency, in November 2018. This study aimed to estimate the genetic parameters of birth weight, average daily gain (ADG), and weaning weight of Padjadjaran sheep. A descriptive method was employed, and data collection was conducted through purposive sampling, utilizing birth weight and weaning weight data from 2016 to 2018. The dataset comprised 66 lambs, comprising 29 male and 37 female progeny from 6 rams and 57 ewes. The heritability estimates for birth weight, pre-weaning ADG, and weaning weight, analyzed using the paternal half-sib correlation method, were 0.30±0.39, 0.24±0.36, and 0.34±0.41, respectively. The highest estimated breeding values (CBVs) for birth weight were observed in ID 1798 (0.39 kg); for pre-weaning ADG, the highest EBVs were in ID 1709 (0.51 kg), 1743 (1.11 kg), 16103 (1.64 kg), and 1788 (1.51 kg). Meanwhile, the highest EBVs were in ID 16103 (2.48 kg). In inclusion, the estimated breeding values for birth weight, pre-weaning ADG, and weaning weight in both male and female Padjadjaran sheep were above the population average, indicating that these traits can be used as selection to enhance productivity in future breeding programs.